Oxford new syllabus Mathematics 2 - Har, Dr Yeap Ban (Karachi : Oxford university press, 2018)
The Oxford New Syllabus Mathematics 2 (7th Edition) is a textbook designed for secondary school students, typically for those in the later years of their education. It builds upon the foundations laid in the first book (Oxford New Syllabus Mathematics 1) and expands into more advanced mathematical topics. The book covers a broad range of mathematical concepts and skills, aiming to develop critical thinking, problem-solving abilities, and a deeper understanding of mathematics.
Keywords: Mathematics : Textbook